PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PT. JAMBI PERMATA TOUR DAN TRAVEL DI SUNGAI PENUH - Gampo Haryono; Susi Evanita (Jurnal Riset Manajemen Bisnis dan Publik, 2015)
This study aimed to analyze: 1) influence of Tangible to customer loyalty PT. Jambi Permata. (2) influence of reliability to customer loyalty PT. Jambi Permata. (3) influence of responsiveness to customer loyalty PT. Jambi Permata (4) influence of assurance customer loyalty PT. Jambi Permata (5) influence of empathy to customer loyalty PT. Jambi Permata. The population in this study are customers of PT. Jambi Permata many as 525 people. Drawn from a population sample of 84 customers. Sampling was done by using accidental sampling technique, in which the sample is based on coincidence, that existing patients at study sites. Data analysis technique used is multiple regression. Further research hypothesis test using t test and F test. The results showed that: (1) Tangible have a significant influence on customer loyalty PT. Jambi Permata. (2) Reliability have a significant influence on customer loyalty PT. Jambi Permata. (3) Responsiveness have a significant influence on customer loyalty PT. Jambi Permata. (4) assurance have a significant influence on customer loyalty PT. Jambi Permata. (5) Empathy have a significant influence on customer loyalty PT. Jambi Permata. Keywords : Tangible , reliability , responsiveness , assurance , empathy , loyality